2019
DOI: 10.1016/j.jwb.2018.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Gender in international business journals: A review and conceptualization of MNCs as gendered social spaces

Abstract: The paper reviews 105 contributions published in journals pertinent to the field of International Business (IB) between 1991 and 2014 and details four main conceptualizations of gender: how women are compared against men, how gender is treated as a control variable and a cultural macro variable, and how gender is 'done' in international organizations. The review reveals that positivist epistemological assumptions dominate the IB field and that the current understanding of gender is limited. To advance the rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 161 publications
(129 reference statements)
0
29
0
Order By: Relevance
“…Consequently, we acknowledge that this could limit the generalizability of our findings to firms located in other countries. Future research would benefit from exploring the implications of female strategic leaders in non-U.S. firms (Bazel-Shoham, Lee, Rivera, & Shoham, 2017;Koveshnikov, Tienari, & Piekkari, 2019). Second, although we paired insights from our interviews with quantitative data, we did not interview individuals within the firms in our quantitative sample.…”
Section: Limitations and Conclusionmentioning
confidence: 99%
“…Consequently, we acknowledge that this could limit the generalizability of our findings to firms located in other countries. Future research would benefit from exploring the implications of female strategic leaders in non-U.S. firms (Bazel-Shoham, Lee, Rivera, & Shoham, 2017;Koveshnikov, Tienari, & Piekkari, 2019). Second, although we paired insights from our interviews with quantitative data, we did not interview individuals within the firms in our quantitative sample.…”
Section: Limitations and Conclusionmentioning
confidence: 99%
“…Finally, a characteristic feature of organizational identity work and neocolonialism in Dancom is that virtually all our research participants were men. Male domination in HQ management is typical of MNCs (Frenkel, 2017) and this is reflected in international business journals that for the most part remain gender blind (Koveshnikov, Tienari, & Piekkari, 2019). We found that tensions and struggles around the identity established at HQ did not undermine male dominance in the various units of the MNC.…”
Section: Discussionmentioning
confidence: 99%
“…'Power distance' (Hofstede, 1980(Hofstede, , 2001 at societal level concerns the extent to which the distribution of power is accepted by the society's members (Ghemawat, 2017) and their endorsement of perceived inequalities (Fowler et al, 2018). Power distance surfaces in the form of perceptions of inequality and perceived asymmetries in country relationships, influencing behaviours of groups (Koveshnikov et al, 2019). Groups such as the MNC that are exposed to multiple cultural contexts, where differences in the distribution of power may coexist, have implications for how key decisions are made (Fowler et al, 2018;Kaasa et al, 2013) and differences in working practices (Ghemawat, 2017;Sutton, 2012;Weber, 2005).…”
Section: Cultural Distance and Mnc Across Bordersmentioning
confidence: 99%
“…Variables were derived from recent empirical research (Kooij et al, 2010;Koveshnikov et al, 2019;Kunze et al, 2011) related to age, diversity, gender, and ethnicity. It argues that older employees can have a beneficial effect on firm productivity because of their experience, loyalty, morals, and work-ethic compared to younger workers.…”
Section: Moderatormentioning
confidence: 99%
See 1 more Smart Citation